2022
DOI: 10.1016/j.jemermed.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade After COVID-19 Vaccination

Abstract: Background Acute pericarditis is a diffuse inflammation of the pericardial sac with many well-defined etiologies. Acute pericarditis as a vaccine-related adverse event is a rare entity and the association between pericarditis and the immunogenic response to COVID-19 vaccines is still being fully characterized. Case Report A previously healthy 18-year-old male presented with fever, pleuritic chest pain, and shortness of breath shortly after receiving the first dose of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For the SARS-CoV-2 pandemic, different types of vaccine are currently available. Increasing concerns about pericarditis and/or myocarditis following the mRNA vaccine injection have been raised [1][2][3][4]. Of note, COVID-19 vaccine-related cardiac involvement usually presents in young men [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the SARS-CoV-2 pandemic, different types of vaccine are currently available. Increasing concerns about pericarditis and/or myocarditis following the mRNA vaccine injection have been raised [1][2][3][4]. Of note, COVID-19 vaccine-related cardiac involvement usually presents in young men [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the benefit of the SARS-CoV-2 vaccine outweighs the risk, more and more adverse events have been reported. The association of SARS-CoV-2 messenger ribonucleic acid (mRNA) vaccines (Pfizer-BioNTech and Moderna) with pericarditis and myocarditis in young adults has been reported, particularly for male adolescents [1][2][3][4]. However, data regarding other types of coronavirus disease 2019 (COVID-19) vaccines, such as the viral vector vaccines, are extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…Email: pathumsook@gmail.com Dear Editor, we would like to share ideas on the publication "Cardiac Tamponade After COVID-19 Vaccination [1]." Hryniewicki et al concluded that "Although a direct causal link cannot be demonstrated, we present this case to increase awareness among emergency physicians of pericarditis as a rare, but potentially serious adverse event associated with COVID-19 vaccination.…”
mentioning
confidence: 91%
“…Hryniewicki et al concluded that "Although a direct causal link cannot be demonstrated, we present this case to increase awareness among emergency physicians of pericarditis as a rare, but potentially serious adverse event associated with COVID-19 vaccination. [1]." We agree that the COVID-19 vaccine might induce some adverse event and cardiac tamponade is possible.…”
mentioning
confidence: 95%
“…1,2 Cardiac tamponade has been reported following mRNAbased COVID-19 vaccination and COVID-19 infection. [3][4][5][6][7][8][9][10] Globally, there have been approximately 596 million cases of COVID-19 and 6.4 million reported deaths as of July 2022. Over 12.6 billion vaccination doses have been provided over 184 countries, which averages to be 161 injections per 100 persons worldwide.…”
Section: Introductionmentioning
confidence: 99%